Space education in Kiruna, Northern Sweden - Sandahl, Ingrid; Wikström, Alf (Advances in Geosciences, 2005)
The town of Kiruna in the north of Sweden has a concentration of space activities and space research with, for example, the Swedish Institute of Space Physics, Esrange, the ESA Salmijärvi satellite station, and EISCAT (European Incoherent Scatter Radar) Scientific Association. The Department of Space Science is a joint department between the two most northern universities in Sweden, Luleå University of Technology and Umeå University in collaboration with the Swedish Institute of Space Physics. It offers a range of education programmes in the space field. There are bachelor and master programmes in space engineering, and a bridging programme for students without a science background from secondary school. The Department also contributes to courses for teachers, Ph.D. courses and secondary school level courses. One master's program and a three week summer course are given entirely in English and welcome international students. Thanks to good cooperation with Esrange students can build and fly experiments on high altitude balloons and sounding rockets and also take a large responsibility for the management of the projects. Close interaction with research and industry is an important part of the education. Validerad; 2005; 20100325 (andbra)